Analisis Peran dan Fungsi Public Relations di Lembaga Pendidikan Islam - Pasha Syahritsa Maulana; Subhan Afifi (Jurnal Mahasiswa Komunikasi Cantrik, 2021)
Islamic Education Institutions are places where the educational process takes place with the aim of changing individual behavior in a better direction through interaction with the surrounding environment, based on Islamic values. In addition to carrying out the teaching and learning process, the Islamic Education Institute manages public relations activities in the form of communication management with the internal public and external public. This study aims to determine the role and function of public relations in Islamic Educational Institutions. The research method used is a case study which is one type of qualitative research method with an interpretive paradigm. The case study was conducted at SDIT in Sleman, Yogyakarta Special Region. The results of this study indicate that schools carry out the roles and functions of public relations management in the form of internal relations and external relations. Internal relations are carried out in various employee relations programs such as providing work motivation and achievement, education and training, as well as special events that strengthen the intimacy of teachers and employees. External relations are run through community relations and government relations programs. Community relations are carried out by establishing good relations with the surrounding community, while government relations are carried out with district government agencies, especially the Education Service.Keywords: public relations, Islamic educational institution, Islamic primary school